Time Serial Pattern of Demand Generation for Public Transportation by New Town Development - Yu, Jeongwhon; Bae, Beomkyu; Kim, Minyoung; Hwang, Seonah (Journal of the Korean Society for Railway, 2022)
This study aims to predict the occurrence of public transportation in early stages of third new town with insufficient public transportation infrastructure and contribute to providing appropriate levels of public transportation, by identifying from smart card data patterns of increase in public transportation traffic in the early stages of second new towns. Development ratio and population indicators were presented as factors that directly affect the increase of public transportation, and new towns were classified into three groups by comparing the development ratio, population, and traffic growth trend by year after first move in. Stages of new city growth were classified by analyzing the characteristics of the development ratio, population, and traffic increase patterns for each group.
Keywords: Curve fitting; Growth stage; Public transportation; Second new town; Smart card data